Foreign Tourist Activity and the Need for Recreation/Rest of Administrative Staff from Selected Universities (as Exemplified by West Pomeranian Voivodship) - Jerzy Eider; Paweł Eider; Małgorzata Paczyńska-Jędrycka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The purpose of this article is to show the need for recreation in the context of foreign leisure trips of administrative staff of selected universities in zachodniopomorskie (West Pomeranian) voivodship. It is an essential element of health behavior of each individual. This work shows the awareness of people in relation to the organization of the rest – taking into account both the destination, means of transport, as well as hotel animations. With regard to the aspect of health, attention should be paid to proper preparation for the trip.